Multidisciplinary studies at Cerro Tapera Vázquez site, Pre-Delta National Park, Argentina: The archaeological, sedimentological and paleobotanical evidence - Bonomo, Mariano (2011)
The initial results of archaeological, sedimentological and paleoethnobotanical studies of Cerro Tapera Vázquez (CTV) archaeological site were analyzed. This research aims to characterize the ceramic, lithic and bone materials recorded at CTV, to establish the chronology of the site and to define the paleoenvironmental context during human occupation of the site. The site is located on the wide alluvial floodplain of the Paraná River. In 2008, 16 m2 were excavated at CTV, and abundant smooth, incised and modeled pottery and numerous bone remains (especially of coypu) were recorded. Radiocarbon dates put past human occupation at between 650 and 520 BP. The paleobotanical evidence establishes that for this period the climatic conditions were colder than at present, while the anthracological record allowed the selection criteria used by the occupants in search of vegetal fuel to be determined. The results reached in this study lead to the conclusion that the pre-Hispanic populations that occupied CTV by the end of the Late Holocene were riverine canoe peoples, with complex ceramic technology and subsistence based on hunting, fishing and probably small-scale horticulture.